Effect of cytomegalovirus infection and leukocyte immunoglobulin like receptor B1 polymorphisms on receptor expression in peripheral blood mononuclear cells. (27th December 2018) - Cadena‐Mota, Sandra; Monsiváis‐Urenda, Adriana; Salgado‐Bustamante, Mariana; Monjarás‐Ávila, César; Bernal‐Silva, Sofía; Aranda‐Romo, Saray; Noyola, Daniel E.
ABSTRACT: Leukocyte immunoglobulin like receptor B1 (LILRB1) plays a significant role in a number of infectious, autoimmune, cardiovascular, and oncologic disorders. LILRB1 expression varies between individuals and may be associated with polymorphisms on the regulatory region of the LILRB1 gene, as well as to previous cytomegalovirus infection. In this study, the contribution of these two factors to LILRB1 expression in peripheral blood mononuclear cells of healthy young adults was analyzed. LILRB1 expression in NK cells, T cells, B cells and monocytes was significantly stronger in individuals who had had cytomegalovirus infection than in those who had not ( P  < 0.001, P  < 0.001, P  < 0.01, and P  < 0.001, respectively). Overall, no differences in LILRB1 expression were observed between individuals with and without GAA haplotypes of the LILRB1 regulatory region. However, when analyzed according to cytomegalovirus infection status, significant differences in LILRB1+ NK cells were observed. A higher proportion of LILRB1+ cells was found in GAA+ than in GAA− individuals who had not been infected ( P  < 0.01), whereas GAA− individuals had a larger proportion of LILRB1+ cells than GAA+ individuals who were cytomegalovirus positive ( P  < 0.01). In conclusion, cytomegalovirus infection has a major effect on LILRB1 expression in NK and other mononuclear cells and polymorphisms in the LILRB1 regulatory region appear to have a modulatory influence over this effect.